2018
DOI: 10.1159/000487032
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial GPR124 Exaggerates the Pathogenesis of Atherosclerosis by Activating Inflammation

Abstract: Background/Aims: Endothelial cell dysfunction is the principal pathological process underlying atherosclerotic cardiovascular disease. G protein-coupled receptor 124 (GPR124), an orphan receptor in the adhesion GPCR subfamily, promotes angiogenesis in the brain. In the present study, we explored the role of endothelial GPR124 in the development and progression of atherosclerosis in adult mice. Methods: Using tetracycline-inducible transgenic systems, we generated mice expressing GPR124 specifically under contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…One recent example is the use of PCSK9 DY -injections into mice expressing GPR124 under control of the Tie-2 promoter. Gong et al found that GPR124, a receptor known to increase angiogenesis in the brain, influences the pathogenesis of atherosclerosis by activating nitrosative stress and NLRP3 inflammasome signaling (50). Nevertheless, while PCSK9 DY itself is suitable to create atherosclerosis models user errors and gender-dependent susceptibility to PCSK9 DY could lead to great variations of study outcomes between laboratories (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…One recent example is the use of PCSK9 DY -injections into mice expressing GPR124 under control of the Tie-2 promoter. Gong et al found that GPR124, a receptor known to increase angiogenesis in the brain, influences the pathogenesis of atherosclerosis by activating nitrosative stress and NLRP3 inflammasome signaling (50). Nevertheless, while PCSK9 DY itself is suitable to create atherosclerosis models user errors and gender-dependent susceptibility to PCSK9 DY could lead to great variations of study outcomes between laboratories (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…The repression of the NLRP3 inflammasome is a critical factor in I/R or inflammation by correlation with SIRT1, which was proved to be involved in both preventing cells from injury induced by various stress and improving endothelial precursor cell function [39,40]. Activating the NLRP3 inflammasome signaling can promote atherosclerosis pathogenesis via the overexpression of inducible endothelial-specific GPR124 [41]. In a previous study of ischemic acute kidney injury (AKI), the deficiency of NLRP3 served as a protective factor against mortality, renal dysfunction, and neutrophil influx of mice [42].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, postnatal or adult GPR124 deletion does not affect BBB integrity 12. Recent studies have highlighted some essential yet long ignored roles played by GPR124 in various pathophysiological processes of cerebrocardiovascular diseases 12,13. For instance, GPR124 receptors are involved in the development of high blood pressure 14,15.…”
Section: Introductionmentioning
confidence: 99%